PFOA biomonitoring and kidney cancer risk: a meta-analysis of serum levels - Spyrakis, Francesca; Tiburtini, Gioele Antonio; Bruno, Stefania; Dragani, Tommaso A.; Colombo, Francesca (Frontiers in Oncology, 2025)
IntroductionThe potential link between perfluorooctanoic acid (PFOA) exposure and kidney cancer risk in humans remains uncertain. This meta-analysis aims to clarify the association by analyzing serum PFOA levels, a direct biomarker of internal exposure, rather than relying on indirect environmental or occupational measures. MethodsA systematic literature search was conducted using PubMed and Web of Science to identify relevant studies. Random-effects models were applied to pool effect estimates for both continuous serum PFOA levels and categorical comparisons (highest vs. lowest exposure groups). Subgroup and sex-stratified analyses were also performed. ResultsThree studies met the inclusion criteria, encompassing 1,011 kidney cancer cases and 2,251 controls. Analysis of continuous PFOA levels yielded a non-significant meta-relative risk (mRR) of 1.05 (95% CI: 0.69–1.60), with substantial heterogeneity. The highest versus lowest exposure comparison also showed no significant association (mRR: 0.98; 95% CI: 0.64–1.50). Sex-stratified results from two studies revealed no significant differences in risk. DiscussionThe findings suggest that any increased kidney cancer risk related to serum PFOA exposure is likely small and not statistically significant based on current evidence. Despite biological plausibility for renal toxicity, epidemiological data remain inconclusive. Further research with larger populations and standardized exposure assessment is needed to determine PFOA’s potential carcinogenic effects on the kidney.